(404) A proposed outline for regional manpower planning in Aswan in U.S.R. مخطط مقترح لتخطيط القوى العاملة الإقليمية في أسوان في الاتحاد السوفيتي - Hamdy, Mostafa (The institute of national planning., 2018)
The study entitled “A Proposed Outline for Regional Manpower Planning in Aswan in U.A.R.” addresses the issue of regional manpower planning through a focus on Aswan as a strategically important region during a period of national economic development and planning. The significance of the study arises from the fact that successful economic and social development programs depend heavily on the availability of adequately trained and appropriately distributed human resources. Therefore, manpower planning represents a critical component of regional development strategies. The study aims to establish an analytical and methodological framework for estimating current and future labor-force requirements in the Aswan region while considering demographic, economic, and structural changes affecting labor demand. It also seeks to examine the relationship between regional development policies and employment structures and to identify mechanisms that can achieve a balance between labor supply and labor demand. The research adopts economic planning methods combined with statistical analysis and forecasting techniques for future manpower requirements. The analysis relies on demographic, educational, labor-market, and economic activity data to assess workforce characteristics. Furthermore, labor categories are classified according to professional levels, skills, and productive sectors in order to identify potential gaps between existing and projected manpower requirements. The findings suggest that effective regional manpower planning requires a reliable and continuously updated information system concerning demographic, educational, and economic characteristics of the labor force. The study also emphasizes the importance of coordination between educational and training policies and the requirements of economic development. The research contributes by providing a practical framework that may support policymakers in designing efficient human-resource allocation strategies and achieving balanced and sustainable regional development.